PENGARUH KEPEMIMPINAN VISIONER, KOMPETENSI PROFESIONAL GURU DAN BUDAYA SEKOLAH TERHADAP MUTU SEKOLAH SMA NEGERI - NURLAELA, NURLAELA; MURNIATI, NGURAH AYU NYOMAN; GINTING , ROSALINA BR (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This research aims to examine and analyze: (1) the influence of the school principal's Visionary Leadership on School Quality, (2) the influence of Teacher Professional Competency on School Quality, (3) the influence of school culture on School Quality, and (4) the influence of the school principal's Visionary Leadership , Teacher Professional Competence and School Culture simultaneously affect School Quality. Population of 519 people, sample of 85 teachers. The instrument test used is the validity and reliability test. The classical assumption test uses the normality test, linearity test, multicollinearity test, and heteroscedasticity test. Data analysis used multiple linear regression tests, F test (ANOVA) and t test. Based on the research results, it can be concluded as follows: (1) The Principal's Visionary Leadership has significant effect on School Quality. This is based on the results of the t test, it is proven that the results of tcount ? ttable are 6.811 ? 1.291. The magnitude of the influence of the Principal's Visionary Leadership on the School Quality variable is 35.8%; (2) Teacher Professional Competence has significant effect on School Quality. This is based on the results of the t test, it is proven that tcount is 12.375 ? 1.291. The magnitude of the influence of Teacher Professional Competency on the School Quality variable is 64.9%; (3) School culture has significant effect on school quality. This is based on the results of the t test, it is proven that tcount = 10.006 > t table 1.291. The magnitude of the influence of School Culture on the School Quality variable is 54.7%; (4) The Principal's Visionary Leadership, Teacher Professional Competence and School Culture simultaneously influence the School Quality variable, obtaining lFcount of 62.886 > lFtable (62.886 > l2.71). The magnitude of the influence of the three independent variables is 68.8%. ABSTRAKPenelitian ini untuk menganalisis: (1) pengaruh Kepemimpinan Visioner kepala sekolah terhadap Mutu Sekolah, (2) pengaruh Kompetensi Profesional Guru terhadap Mutu Sekolah, (3) pengaruh budaya sekolah terhadap Mutu Sekolah, dan (4) pengaruh Kepemimpinan Visioner kepala sekolah, Kompetensi Profesional Guru dan Budaya Sekolah secara simultan terhadap Mutu Sekolah. Populasi 519 orang, sampel sebanyak 85 orang guru. Uji instrumen yang digunakan adalah uji validitas dan reliabilitas. Uji asumsi klasik menggunakan uji normalitas, uji linearitas, uji multikolinearitas, dan uji heteroskedastisitas. Analisis data menggunakan uji regresi linier berganda, uji F (ANOVA) dan uji t. Berdasarkan hasil penelitian dapat disimpulkan sebagai berikut: (1) Kepemimpinan Visioner Kepala Sekolah berpengaruh positif dan signifikan terhadap Mutu Sekolah. Hal ini berdasar hasil Uji t, terbukti hasil thitung ? ttabel yaitu 6,811 ? 1,291. Besarnya pengaruh Kepemimpinan Visioner Kepala Sekolah terhadap variabel Mutu Sekolah adalah 35,8%; (2) Kompetensi Profesional Guru berpengaruh positif dan signifikan terhadap Mutu Sekolah. Hal ini berdasarkan hasil uji t terbukti thitung sebesar 12,375 ? 1,291. Besarnya pengaruh Kompetensi Profesional Guru terhadap variabel Mutu Sekolah adalah 64,9% ; (3) Budaya Sekolah berpengaruh positif dan signifikan terhadap Mutu Sekolah. Hal ini berdasarkan hasil uji t terbukti thitung = 10,006 > t table 1,291. Besarnya pengaruh Budaya Sekolah terhadap variabel Mutu Sekolah adalah 54,7% ; (4) Kepemimpinan Visioner Kepala Sekolah, Kompetensi Profesional Guru dan Budaya Sekolah secara simultan berpengaruh terhadap variabel Mutu Sekolah diperoleh lFhitung sebesar 62,886 > lFtabel (62,886 > l2,71). Besarnya pengaruh dari ketiga variabel bebas adalah sebesar 68,8%.